IDENTIFIKASI AVIFAUNA KAWASAN GUNUNG DEMPO KOTA PAGAR ALAM PROVINSI SUMATERA SELATAN - Fahmy Armanda (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
Identification is part of the classification of living things. The classification of living things is the formation of groups of various types of animals and plants on earth so that the taxa are arranged in an orderly manner following a hierarchy. The traits or characteristics that are the basis for classification vary depending on the goals to be achieved. One of the characters that can be used as a basic criterion for classifying avifauna is morphological characters. This research aims to determine the avivauna species in the Mount Dempo area, Pagar Alam City, South Sumatra. This research is descriptive qualitative in nature. The sampling technique is quota sampling and the Miles and Huberman model data analysis technique. The results of identification research in the Mount Dempo area obtained 21 types of avifauna (birds) in the Mount Dempo area, Pagar Alam City, South Sumatra Province, and 9 types that were not identified from interviews with local residents. The diversity index of avifauna (bird) species in the Mount Dempo area, Pagar Alam City, South Sumatra Province is 2.67753, which means that the diversity of avifauna (bird) species is moderate.